2008
DOI: 10.1128/jb.00437-08
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulation of the DnaJ Homolog CbpA by the Global Regulators σ S and Lrp, by the Specific Inhibitor CbpM, and by the Proteolytic Degradation of CbpM

Abstract: CbpA is a DnaJ homolog that functions as a DnaK cochaperone. Several cellular processes, including growth at low and high temperatures and septum formation during cell division, require either CbpA or DnaJ. CbpA is encoded in an operon with the gene for CbpM, which is a specific in vivo and in vitro inhibitor of CbpA. Here, we have cooverexpressed CbpA with CbpM in a ⌬cbpAM ⌬dnaJ strain and examined the resulting phenotypes. Under these conditions, sufficient free CbpA activity was present to support growth at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…19 It is known that CbpA and CbpM are co-expressed and accumulate to similar levels in the stationary phase of cell growth. 22 It was shown also that CbpM regulates the DNA-binding activity of CbpA, 18 and it was suggested that the inhibitory effect of CbpM on CbpA might prevent DnaK from interacting with the specific set of substrates in the cell. 22 However, the molecular mechanism underlying this inhibition is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 It is known that CbpA and CbpM are co-expressed and accumulate to similar levels in the stationary phase of cell growth. 22 It was shown also that CbpM regulates the DNA-binding activity of CbpA, 18 and it was suggested that the inhibitory effect of CbpM on CbpA might prevent DnaK from interacting with the specific set of substrates in the cell. 22 However, the molecular mechanism underlying this inhibition is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, CbpM interaction with CbpA is known to inhibit the DNA binding of CbpA. 21,22 DNA does not bind the J-domain but the region C-terminal to the Jdomain of CbpA, 19 suggesting additional role of this region in regulation by CbpM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First identified as a DNA binding protein, E. coli CbpA binds DNA efficiently, with a preference for curved DNA, and has been localized to the nucleoids of stationaryphase cells (1,16,30). More recent studies have revealed that E. coli CbpA can function as a cochaperone for the DnaK/ Hsp70 chaperone system, and its activity can be modulated by CbpM, an 11-kDa protein that has structural homology to DafA of Thermus thermophilus (2,6,7,8).…”
mentioning
confidence: 99%
“…[11][12][13][14] The cbpA and cbpM genes form an operon and are co-expressed, and examination of sequenced genomes reveals that this operon is found in a wide variety of bacteria. 12,13 The molecular surface of CbpA that is bound by CbpM locates to the J-domain and primarily consists of positively charged amino acids (R26, R30, and H33) 7,11 (Fig.…”
mentioning
confidence: 99%